1994
DOI: 10.1111/j.1432-1033.1994.tb18649.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and nucleotide sequence of the Pseudomonas aeruginosa glucose‐selective OprB porin gene and distribution of OprB within the family Pseudomonadaceae

Abstract: OprB is a glucose-selective porin known to be produced by Pseudomonas aeruginosa and Pseudomonas putida. We have cloned and sequenced the oprB gene of I? aeruginosa and obtained expression of OprB in Escherichia coli. The mature protein consists of 423 amino acid residues with a deduced molecular mass of 47597 Da. Several clusters of amino acid residues, potentially involved in the structure or function of the protein, were identified. An area of regional homology with E. coli LamB was also identified. Carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The cloning and nucleotide sequence of the P. aeruginosa oprB gene have been previously described (36). The allele replacement technique of Schweizer (26) was used to construct a defined OprB-lacking mutant strain.…”
Section: Resultsmentioning
confidence: 99%
“…The cloning and nucleotide sequence of the P. aeruginosa oprB gene have been previously described (36). The allele replacement technique of Schweizer (26) was used to construct a defined OprB-lacking mutant strain.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible that one of the many genes encoding hypothetical proteins identified in this study encodes one of these two enzymes. Also a sugar ABC transporter gene cluster (PP1015-PP1019; Wylie & Worobec, 1994, 1995 was identified that was specifically induced upon growth on glucose (Table 3). This gene cluster encodes a glucose porin and a sugar transporter, of which the sugarbinding protein (PP1015) is very likely the previously purified glucose-specific glucose binding protein (Stinson et al, 1977), as this gene encodes a protein of a similar size as the purified protein (44?5 kDa) and has a similar amino acid composition.…”
Section: Hcamentioning
confidence: 99%
“…The full complement of genes and protein components of this system has not been described. Presumably, two of the genes regulated by GltR are oprD, which encodes a glucose-specific porin (23,24), and the yet to be identified gene for GBP (gltB). The OmpR subfamily of these proteins control a variety of systems in different bacteria, including those involved in response to medium osmolarity, phosphate uptake, virulence, and antibiotic resistance (12).…”
mentioning
confidence: 99%